Adaptation, Resilience and CAP Reform: A Comparison of Crofts and Livestock Farms in Scotland. (2nd October 2017) - Sutherland, Lee-Ann; Hopkins, Jonathan; Toma, Luiza; Barnes, Andrew; Matthews, Keith
ABSTRACT: In this paper, we assess the recent and anticipated changes on Scotland's livestock-producing crofts, using a representative survey of Scottish farmers undertaken in 2013. We find that crofters are similar to other livestock farmers, both inside and outside of the traditional crofting counties, in terms of age, years of involvement in the holding and percentage of identified successors, but are less likely to own their holdings or to operate them for profit. Crofters reported being more subsidy dependent than other livestock producers, and many appear likely to retreat from crofting in the event of substantive subsidy reductions. However, crofting respondents identified input costs, regulations, commodity prices and climate change as having had greater influence on how they manage their crofts than the 2005 transition to the 'Single Farm Payment'. Overall, crofters reported making fewer changes than their counterparts in non-crofting counties, but similar levels to those of other livestock farmers within crofting counties, suggesting less 'room for manoeuvre' within the remote areas in which most crofts are located. However, there is some evidence that 'active' crofts are 'bouncing forward' in response to recent challenges, particularly into forestry and agri-tourism, also reporting significantly higher perceived economic prospects.